1901 Ariz. Sess. Laws 1252 - (:unkn) unknown (My University, 1901)
§ 391: Required the keeper of every hotel, boarding house, and drinking saloon to post in a conspicuous place in the bar or reception room that travelers divest themselves of weapons. Violators fined five dollars.
Keywords: SENSITIVE PLACES